2017
DOI: 10.1039/c7ta08153g
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of exfoliated 1T MoS2@CNT-based bifunctional separators for lithium sulfur batteries

Abstract: 1T exfoliated MoS2@CNT-based bifunctional separators in a tandem configuration delivered excellent electrochemical performance, and rational guidelines for preparing bifunctional separators for lithium sulfur batteries were suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 63 publications
0
63
0
Order By: Relevance
“…On the other side, researchers applied the metallic (1T) phase MoS 2 rather than the normals emicon-ducting( 2H)p hase MoS 2 as the interlayer,w hich had much bettere lectron conductivity than the 2H phase MoS 2 . [51] The 1T phase MoS 2 exhibited around6 70 mAh g À1 capacity after 500 cycles under 1C rate. There was considerable variation in absorption between semiconducting phase (2 H) andm etallic phase (1T) of MoS 2 towards PS based on DFT simulation (see Figure 5b,d).…”
Section: Functional Interlayers and Separator-additives During The Elmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other side, researchers applied the metallic (1T) phase MoS 2 rather than the normals emicon-ducting( 2H)p hase MoS 2 as the interlayer,w hich had much bettere lectron conductivity than the 2H phase MoS 2 . [51] The 1T phase MoS 2 exhibited around6 70 mAh g À1 capacity after 500 cycles under 1C rate. There was considerable variation in absorption between semiconducting phase (2 H) andm etallic phase (1T) of MoS 2 towards PS based on DFT simulation (see Figure 5b,d).…”
Section: Functional Interlayers and Separator-additives During The Elmentioning
confidence: 95%
“…Soluble PS diffused from dark PS-containing electrolyte in the right to the left vial through the a) PP separatora nd b) 1T-MoS 2 functional interlayer for 24 hours. [51] c) SEM images of Li metali nPPa nd functional separators. [47] d) Infiltration of the electrolyte on PP separator,f unctional separators with the corresponding contact angels and e) their thermal stability (treated 2min at 150 8C).…”
Section: D Phosphide-based Materialsmentioning
confidence: 99%
“…[35,86] For instance, Jeong et al reported that the electrochemical performance of MoS 2 wass trongly dependent on its phase, if usedf or LiÀSb atteries. [87] Theoretical analysis indicates that both 1T MoS 2 and 2H MoS 2 have strongi nteractions with the soluble polysulfide species (Figure 12 a). Although the interaction energies of adsorption toward Li 2 S 4 and Li 2 S 6 are similar for 2H and 1T MoS 2 ,t he 1T MoS 2 phase performs better than that of 2H MoS 2 because of improved surface reactionk inetics.…”
Section: Phase Engineeringmentioning
confidence: 98%
“…Reproduced with permission. [87] Copyright 2017, The RoyalS ociety of Chemistry.b)Aschematic illustration of the conversion of LiPSs on 1T MoS 2 /graphenea nd the measured cycling performanceoft he Li 2 S 6 cathode. Reproducedw ith permission.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…[29] These can be generalized into three strategies using MoS 2 :p rotection by augmenting the separator,t he Li-metala node, and PS trapping by inclusion in ac omposite cathode. Specific examples have included use of MoS 2 as as eparator coating, [30][31][32][33][34][35] as ap rotective layer on the anode, [36,37] and inclusion in ac omposite cathode. This composite cathode is generally fabricated using ac arbonbased support, such as ag raphene nanosheet, [23] carbon cloth, [38] reduced graphene oxide, [39][40][41][42] or an itrogen-doped support such as carbon nanotubes (CNTs), [35] mesoporous carbon spheres, [38] reduced graphene oxide, [43] or porous carbon.…”
Section: Introductionmentioning
confidence: 99%